2021
DOI: 10.32859/era.22.24.1-71
|View full text |Cite
|
Sign up to set email alerts
|

First insight on ethnobotanical appraisal of plants used traditionally as medicine by Berber community (Amazigh-speaking), living in Driouch province (North-eastern Morocco)

Abstract: Background: Most ethnobotanical studies carried out in different regions of Morocco revolved around documentation of medicinal plants and their medical uses. However, little is known about ethnobotanical knowledge coupled to Berber community living in "Driouch province" (Northeastern region of Morocco). This study aimed to identify and document medicinal plants used traditionally by local people to manage health problems while investigating and comparing ethnobotanical patterns obtained in this region with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Other ethnobotanical investigations conducted in the Rif (Chaachouay et al, 2019b) and in other zones of Morocco (Salhi et al, 2011;El Hachlafi et al, 2020;Najem et al, 2022) also demonstrated that leaves were the most cited part by the majority of respondents. In addition to other regions, such as Turkey and Pakistan, as well as Italy (Ajjoun et al, 2021), the high frequency of leaf utilization can be explained by the collection speed and ease (El Hafian et al, 2014).…”
Section: Plant Parts Used Preparation and Administrationmentioning
confidence: 99%
“…Other ethnobotanical investigations conducted in the Rif (Chaachouay et al, 2019b) and in other zones of Morocco (Salhi et al, 2011;El Hachlafi et al, 2020;Najem et al, 2022) also demonstrated that leaves were the most cited part by the majority of respondents. In addition to other regions, such as Turkey and Pakistan, as well as Italy (Ajjoun et al, 2021), the high frequency of leaf utilization can be explained by the collection speed and ease (El Hafian et al, 2014).…”
Section: Plant Parts Used Preparation and Administrationmentioning
confidence: 99%